Cash on Delivery in E-Commerce Indonesia: A Solution or a problem? - Dirkareshza, Rianda; Witarso, Laurentius Sandi; Permatasari, Elizabet Devi; Indra, Rafael (Widya Yuridika, 2025)
Cash on Delivery (COD) is one of the frequently utilized payment methods in Indonesian e-commerce, enabling buyers to settle payments for purchased goods upon their arrival at the designated address. However, the limited comprehension among the public regarding the COD mechanism gives rise to various legal predicaments, encompassing both criminal and civil aspects. This research endeavors to ascertain the psychological state of logistics partners who fall victim to consumers misconstruing the COD process, the legal quandaries prompted by COD, and legal remedies to these issues. Employing the normative juridical method with a statutory approach, supplemented by concepts, cases, and interviews, this study finds that, according to the Job Stress Scale measuring instrument, couriers experiencing a substantial volume of daily COD deliveries endure significant stress levels at 58.5%. The stress among couriers emanates from rampant instances of legal transgressions associated with COD, encompassing both criminal and civil domains. Consequently, addressing this challenge necessitates the provision of alternative payment modes such as bank transfers, digital wallets, or installment payments. Furthermore, the establishment of specialized COD regulations is imperative to mitigate the likelihood of similar occurrences in the future.